IMPROVING PRODUCTIVITY IN A POOR WORK CULTURE IN THE WORLD OF CONSTRUCTION - Kenzo, Himalaya Bima; Pratama, Oktioza; Apfiasari, Steela; Yulaikah, Yulaikah; Maryani, Edna (Journal of Industrial Engineering & Management Research, 2025)
A good work environment is a key factor in fostering a positive work culture in the construction industry. According to a study conducted by the Ministry of Public Works and Public Housing (PUPR), approximately 45% of construction workers feel that an uncomfortable work environment contributes to their low productivity (PUPR, 2022). Unsafe work environments, such as lack of protection from extreme weather and inadequate health facilities, can lead to stress and dissatisfaction among workers. For example, a building construction project in Jakarta carried out by PT XYZ experienced delays because workers lacked adequate access to rest areas and proper sanitation. This demonstrates that investing in good facilities can improve worker comfort and productivity. Training and skills development also play a crucial role in fostering a work culture. Data from the National Professional Certification Agency (BNSP) shows that only 30% of construction workers receive adequate training in their field (BNSP, 2023). Lack of training can lead to workers feeling insecure in carrying out their tasks, which in turn can reduce productivity. For example, a building renovation project in Surabaya experienced numerous technical errors due to workers lacking sufficient skills in using heavy equipment. Therefore, construction companies need to invest in ongoing training programs to improve workers’ skills and knowledge.